2010
DOI: 10.1002/eqe.1088
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of fundamental frequency drop for unreinforced masonry buildings from dynamic tests

Abstract: The knowledge of fundamental frequency and damping ratio of structures is of uppermost importance in earthquake engineering, especially to estimate the seismic demand. However, elastic and plastic frequency drops and damping variations make their estimation complex. This study quantifies and models the relative frequency drop affecting low-rise modern masonry buildings and discusses the damping variations based on two experimental data sets: Pseudo-dynamic tests at ELSA laboratory in the frame of the ESECMaSE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 28 publications
3
32
0
Order By: Relevance
“…The noise measurements showed that first vibration modes are in the range 4-6 Hz for both buildings. Even considering a small reduction (about 20 %) of the vibration frequencies during earthquakes because of the nonlinear behavior of masonry structures (Michel et al 2011), resonance phenomena must have occurred during 2009 earthquake, thus justifying the anomalous damage suffered by the two villages.…”
Section: Discussionmentioning
confidence: 99%
“…The noise measurements showed that first vibration modes are in the range 4-6 Hz for both buildings. Even considering a small reduction (about 20 %) of the vibration frequencies during earthquakes because of the nonlinear behavior of masonry structures (Michel et al 2011), resonance phenomena must have occurred during 2009 earthquake, thus justifying the anomalous damage suffered by the two villages.…”
Section: Discussionmentioning
confidence: 99%
“…However, a well-known drawback of ambient vibration measurements is the very low amplitude of excitation, resulting in mostly linear responses. In addition, despite controversial results, modal properties derived from ambient vibrations have been shown in the past to be potential indicators of structural damage (Mucciarelli et al, 2004;Clinton et al, 2006;Michel et al, 2011). As a consequence, many proposals for structural identification based on vibrations measurements for damage detection have emerged (Chellini et al, 2010;Moaveni et al, 2010;Behmanesh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, frequency is representative of the linear elastic structural response only. Although the real frequency related to higher excitation amplitudes will be lower than the frequency characterizing the ambient vibration response, approximate relationships between the two frequencies are available [11]. Also, it is assumed that the retrofit will remain at least equally sound as the rest of the structure during an earthquake.…”
Section: Discussionmentioning
confidence: 99%